The role of personality in the family stress model on mothers : an Asian context - Chong, Bryan Wei Ren (2017)
Empirical evidence has shown that mothers play an instrumental role in the development of children. The negative effects of poor parenting behaviours on the outcomes of the child highlight the importance of understanding the antecedents of parenting behaviours. By doing so, better child outcomes may be achieved by mitigating the factors that influence such behaviours. This study had two aims: testing the link between income-stress-parenting behaviours-child outcomes as proposed by the family stress model and testing the moderating role of personality. Using the family stress model as the theoretical basis, it was hypothesized that family income is negatively associated with parental stress (Hypothesis 1), parental stress is negatively associated with positive parenting (Hypothesis 2), and positive parenting is positively associated with child behavioural outcomes (Hypothesis 3). The personality trait conscientiousness (Hypothesis 4a) and neuroticism (Hypothesis 4b) were proposed to moderate the relationship between parental stress and positive parenting. Survey data were collected via an online survey from 101 mothers. Results supported the hypotheses drawn from the family stress model. However, personality has no moderating effect on the parental stress-parenting behaviour relationship, suggesting that parental stress-parenting behaviour relationship is universal. Practical implications, limitations, and directions for future research are discussed. Keywords: family stress model, family income, parental stress, positive parenting, child behavioural outcomes, mothers, personality